PENINGKATAN KETERAMPILAN PEMUDA KARANG TARUNA DESA BEJI MELALUI PELATIHAN TEKNISI KOMPUTER - Gustin Setyaningsih; Ito Setiawan; Muhamad Awiet Wiedanto Prasetyo; Ranggi Prahraningtyas Aji; Nabila Aprilianti (Universitas Sanata Dharma, 2019)
Karang Taruna aims to realize the growth and development of every member of society who is qualified, skilled, intelligent, innovative, characterized and has social awareness and responsibility in preventing, counteracting, overcoming and anticipating various social welfare issues, especially the younger generation, the quality of social welfare of each member the community, especially the younger generation in the village / kelurahan in an integrated, directed, comprehensive and sustainable manner, the development of business towards the independence of every member of the community, especially the younger generation and the development of partnerships that ensure increased capability and potential of young people in a directed and sustainable manner. This is reflected in the vision of cadets by Beji Village 5, namely: